2021
DOI: 10.1371/journal.pone.0257380
|View full text |Cite
|
Sign up to set email alerts
|

Suggested visual blockade during hypnosis: Top-down modulation of stimulus processing in a visual oddball task

Abstract: Several theories of hypnosis assume that responses to hypnotic suggestions are implemented through top-down modulations via a frontoparietal network that is involved in monitoring and cognitive control. The current study addressed this issue re-analyzing previously published event-related-potentials (ERP) (N1, P2, and P3b amplitudes) and combined it with source reconstruction and connectivity analysis methods. ERP data were obtained from participants engaged in a visual oddball paradigm composed of target, sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 83 publications
2
11
0
1
Order By: Relevance
“…In previous hypnosis studies conducted in our lab, we found significant modulations of electrophysiological brain responses after hypnotic suggestions with an effect size of d = 0.7 (Franz et al, 2020(Franz et al, , 2021Schmidt, Hecht et al, 2017). To detect an effect of at least this size based on an alpha level of α = 0.05 and a power level of 1β = 0.95, a total of 24 participants is required according to G*Power (Faul et al, 2009).…”
Section: Participantsmentioning
confidence: 95%
“…In previous hypnosis studies conducted in our lab, we found significant modulations of electrophysiological brain responses after hypnotic suggestions with an effect size of d = 0.7 (Franz et al, 2020(Franz et al, , 2021Schmidt, Hecht et al, 2017). To detect an effect of at least this size based on an alpha level of α = 0.05 and a power level of 1β = 0.95, a total of 24 participants is required according to G*Power (Faul et al, 2009).…”
Section: Participantsmentioning
confidence: 95%
“…There were several stages of attentional processing when simulating visual field defects. 46 , 47 First, information inputs under simulated defect conditions captured attention through initial perceptual processing (indexed by N1) to form preliminary representations in the occipital cortex. Second, the higher prefrontal cortex evaluated visual representations and gave forward feedback to the occipital cortex to reactivate visual representations (indexed by P2).…”
Section: Discussionmentioning
confidence: 99%
“…The results show the neuronal dissociation between perceiving the visual objects on the screen and attending them in order to count them, reflected in early and late event-related EEG signals. In a subsequent analysis, we found that this effect was driven by a top-down modulation, reflected in reduced directed information flow from parietal attentional to frontal executive sources during processing of target stimuli ( Franz et al, 2021 ).…”
Section: Blocking Sensory Perception Under Hypnosismentioning
confidence: 91%
“…In three separate EEG studies, I blocked sensory perception of visual, pain, and auditory stimuli using hypnotic suggestions of a wooden board in front of participants’ eyes, a cooling and numbing glove on participants’ hands and earplugs in participants’ ears, respectively ( Figure 1 ; Schmidt et al, 2017b ; Franz et al, 2020 , 2021 ). We used a sensory paradigm that is very common in EEG research with frequent and rare stimuli, called oddball paradigm.…”
Section: Blocking Sensory Perception Under Hypnosismentioning
confidence: 99%